CHARACTERIZATION OF GOLD NANOPARTICLES FROM CLOVE FLOWER WATER EXTRACT AND ITS ANTIOXIDANT ACTIVITY - Gusti Ayu Dewi Lestari; Kadek Duwi Cahyadi; Iryanti Eka Suprihatin (Jurnal Sains Materi Indonesia, 2021)
CHARACTERIZATION OF GOLD NANOPARTICLES FROM CLOVE FLOWER WATER EXTRACT AND ITS ANTIOXIDANT ACTIVITY. Green chemistry is a safe and cost effective method for producing metal nanoparticles, characterize and tested the antioxidant activity of gold nanoparticles (AuNPs). In this research gold nanoparticles were synthesized using HAuCl₄ as the gold precursor and water extract of Syzygium aromaticum (L.) flowers 0.5% as the bioreductor. Characterization of the gold nanoparticles was carried out using UV-Vis spectrophotometer to measure the maximum wavelength, zeta analyzer to determine the particle size, and SEM EDS to investigate the morphology and content of the gold nanoparticles. The antioxidant activity was determined by measuring its free radical scavenging activity using the DPPH method. The research found the AuNPs has a maximum wavelength at 533 nm, and particle size of 73.52 nm. Furthermore, the AuNPs show free radical scavenging activities of up to 70%.